LIFELONG LEARNING MANAGEMENT SYSTEM IN VIDZEME REGION - Cakula, Sarma; Osis, Kaspars; Kapenieks, Atis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
In today’s rapidly changing environment, lifelong learning is becoming an important part of education system. There is no comprehensive strategy or technological support for lifelong learning in the Latvian regions which could upgrade people’s competences and allow them to combine learning with workand family life. It is significant to develop a framework encompassing identification of required competencies, technological support for lifelong learning and make it as part of an ongoing process. The goal of the paper is to create a theoretical framework lifelong learning management technological model and prototype for the Vidzeme region. The focus of the paper is identifying the major steps and elements required to design and incorporate latter mentioned lifelong learning process and particularly adult education perspective supporting technological model in the Vidzeme region. Theoretical framework has been conducted regarding different adult education supporting technological platforms and adult education processing in European Union’s regional context. The paper represents the theoretical preconditions for qualitative development of lifelong learning in the region and presents a technological model prototype which would provide the lifelong learning process with ongoing technological support.